Pengaruh Kualitas Produk, Persepsi Harga Dan Periklanan Terhadap Loyalitas Pelanggan Pada Liyanti Beauty Store Di Kota Blora - Liyanti Ayu Sari (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
Objective of this study: To determine the influence of product quality on customer loyalty. To determine the influence of price perception on customer loyalty. To determine the influence of advertising on customer loyalty. This research uses a quantitative approach. Sampling techniques used are nonprobability sampling with random samplings, while the researcher deliberately determine their sample according to the area and qualified by some requirements. Population of this study is all gender aged 15 - 45 years and customer of Liyanti Beauty Store in Blora City, Central Java, sample of this research amounted to 90 respondents. Data collection method used is a scale with a dependent variable is customer loyalty and its independent variables, i.e., product quality, price perception, and advertising. Data analysis techniques use a double linear regression analysis test with application of the Statistical Package for Social Sciences (SPSS) 22.0 for Windows program. The result of this research : Product quality has the most influence over customer loyalty. Price perception has no influence on customer loyalty. Advertising has no influence on customer loyalty. While the results of research simultaneously show that product quality, price perception, and advertising influence over customer loyalty.